Lama menderita diabetes mellitus tipe 2 sebagai faktor risiko neuropati perifer diabetik - Galvani Volta Simanjuntak; Marthalena Simamora (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Sensory neuropathy in type 2 diabetes mellitus and its correlation with duration of diseaseBackground: Diabetic peripheral neuropathy is a complication of type 2 diabetes mellitus (T2DM) that results in harm to the nervous system. It is a progressive disease, and symptoms get worse over time.Purpose: To exploration the sensory neuropathy in type 2 diabetes mellitus and its correlation with duration of disease.Method: An observational analytic with cross sectional design with population was patients with T2DM without diabetic ulcers in diabetic clinic Sari Mutiara Hospital. The number of samples was 86 respondents by a simple random sampling. Measuring the risk of diabetic peripheral neuropathy used 10 gram monofilament.Results: Showed the majority of the duration of T2DM >5 years (53,5%) and the majority of respondents had neuropathy (54,7%). The results of the Spearman rank correlation test showed that there was a significant correlation between duration of T2DM and risk of diabetic peripheral neuropathy (p-value = 0,023 and r= -0,438). Conclusion: The majority respondents has a diabetic peripheral neuropathy and also has a risk of diabetic peripheral neuropathy who are suffering >5 years. It is recommended that they need a regularly asses and educate to prevent further complication.Keywords: Sensory neuropathy; Type 2 diabetes mellitus; Duration of diseasePendahuluan: Neuropati perifer diabetes adalah komplikasi diabetes yang mengakibatkan kerusakan sistem saraf. Ini adalah penyakit progresif, dan gejalanya bertambah buruk seiring waktu.Tujuan: Untuk mengetahui hubungan lama menderita dengan risiko neuropati pada pasien DM tipe 2.Metode: Desain analitik korelasi dengan pendekatan cross sectional dan populasinya seluruh pasien DM tipe 2 yang tidak memiliki ulkus diabetik di klinik diabetes RSU Sari Mutiara. Sampelnya sebanyak 86 yang diambil dengan teknik simple random sampling. Risiko neuropati perifer diabetik diukur menggunakan monofilament 10 gram.Hasil: Analisis data menunjukkan mayoritas pasien menderita DM tipe 2 yang >5 tahun (53,5%) dan mayoritas pasien telah mengalami neuropati (54,7%). Hasil uji statistik menggunakan korelasi spearman menunjukan adanya hubungan lama menderita DM tipe 2 dengan risiko neuropati (p-value = 0,023<0,05 dan nilai r = -0,438).Simpulan: Mayoritas responden yang mengalami Neuropati perifer diabetes maupun resiko terjadinya Neuropati perifer diabetes pada mereka kelompok yang menderita DM tipe 2 yang >5 tahun. Sangat dianjurkan pada pasien tersebut untuk dilakukan pengkajian secara teratur dan pendidikan untuk mencegah komplikasi lebih lanjut.